Differing Complex Microbiota Alter Disease Severity of the IL-10−/− Mouse Model of Inflammatory Bowel Disease - Hart, Marcia L.; Ericsson, Aaron C.; Franklin, Craig L. (Frontiers in Microbiology, 2017)
It is estimated that 1.4 million people in the United States suffer from Inflammatory Bowel Disease (IBD), with an overall annual health care cost of more than 1.7 billion. Although the exact etiology of this disease remains unknown, research suggests that it is a multifactorial disease associated with aberrant gastrointestinal microbial populations (dysbiosis). The C57BL/6 and C3H/HeJBir mouse strains with targeted mutations in the IL-10 gene are commonly used models to study IBD. However, anecdotally, disease phenotype can vary in severity from lab to lab. Moreover studies using germfree and monocolonized mice have suggested that gut microbiota (GM) are critical to disease induction in these models. With recent studies suggesting variation in naturally occurring GM composition and complexity among mouse producers, we hypothesized that differences in these naturally occurring complex GM profiles may modulate disease severity in the IL-10-/- mouse model. To test this hypothesis, we use a technique referred to as complex microbiota targeted rederivation (CMTR) to transfer genetically identical C57BL/6 IL-10-/- and C3H/HeJBir IL-10-/- embryos into surrogate CD-1 or C57BL/6 dams from different commercial producers with varying microbiota complexity and composition. We found that disease severity significantly and reproducibly differed among mice in both IL-10-/- strains, dependent on differing maternally inherited GM. Furthermore, disease severity was associated with alterations in relative abundance of several physiologically relevant bacterial species. These findings suggest that the composition of the resident GM is a primary determinant of disease severity in IBD and provide proof-of-concept that CMTR can be used to investigate the contribution of contemporary complex GM on disease phenotype and reproducibility.